Evidence‐Based Practice to Improve Outcomes for Late Preterm Infants. Issue 1 (19th January 2015) - Baker, Brenda
ABSTRACT: Infants born between 34 weeks 0 days to 36 weeks 6 days gestation have been identified as late preterm infants (LPIs) and account for 70% of preterm births and 9% of all births. The rise in elective deliveries in the past decade is believed to have contributed to the number of late preterm births. An interprofessional team including labor and delivery, neonatal intensive care, and postpartum care providers collaborated to address this issue at an urban academic medical center.